Methylglyoxal activates osteoclasts through JNK pathway leading to osteoporosis. (1st August 2019) - Lee, Kwan Ming; Lee, Cheuk Yan; Zhang, Ge; Lyu, Aiping; Yue, Kevin Kin Man
Abstract: Diabetes mellitus is characterized by chronic hyperglycemia and its diverse complications. Hyperglycemia is associated with inflammatory responses in different organs, and diabetic patients have a higher risk of bone fracture due to increased bone weakness. Methylglyoxal, a reactive advanced glycation end product precursor, is known to have increased level in diabetic patients. The accumulation of methylglyoxal promotes inflammation and it may play a role in diabetes related osteoporosis. In this study, therefore, the underlying mechanism of methylglyoxal on osteoporosis was studied using both animal and cell models. In the animal model, rats were treated with either methylglyoxal or saline as control. In the cell model, the macrophage RAW264.7 was treated with methylglyoxal or vehicle control. Following the treatment, animal samples were harvested for micro-CT and real-time polymerase chain reaction analyses. Cell samples were harvested for MTT assay, RT-PCR, and Western Blotting analyses. In both animals and cell cultures, methylglyoxal was shown to induce osteoclastogenesis by increased gene expression of osteoclast bone biomarkers CTSK, OSCAR and TRACP5. Furthermore, in methylglyoxal-treated macrophages activation of the c-Jun N-terminal kinases signaling pathway was observed, and inhibition of JNK activities resulted in down-regulation of osteoclast biomarkers gene expressions. Our results therefore suggested that methylglyoxal may contribute to the progression of diabetes-related osteoporosis and imbalanced bone remodeling through JNK pathway in osteoclasts. Highlights: Methylglyoxal (MG) triggered bone loss in rats. MG induced osteoclastogenesis. MG increased gene expression of osteoclast bone biomarkers CTSK, OSCAR and TRACP5. MG results in imbalanced bone remodeling through JNK pathway in osteoclasts. MG may contribute to diabetes-related osteoporosis.